Single cell RNA sequencing reveals hemocyte heterogeneity in Biomphalaria glabrata: Plasticity over diversity - Pichon, Rémi; Pinaud, Silvain; Vignal, Emmanuel; Chaparro, Cristian; Pratlong, Marine; Portet, Anaïs; Duval, David; Galinier, Richard; Gourbal, Benjamin (Frontiers in Immunology, 2022)
The freshwater snail Biomphalaria glabrata is an intermediate host of Schistosoma mansoni, the agent of human intestinal schistosomiasis. However, much is to be discovered about its innate immune system that appears as a complex black box, in which the immune cells (called hemocytes) play a major role in both cellular and humoral response towards pathogens. Until now, hemocyte classification has been based exclusively on cell morphology and ultrastructural description and depending on the authors considered from 2 to 5 hemocyte populations have been described. In this study, we proposed to evaluate the hemocyte heterogeneity at the transcriptomic level. To accomplish this objective, we used single cell RNA sequencing (scRNAseq) technology coupled to a droplet-based system to separate hemocytes and analyze their transcriptome at a unique cell level in naive Biomphalaria glabrata snails. We were able to demonstrate the presence of 7 hemocyte transcriptomic populations defined by the expression of specific marker genes. As a result, scRNAseq approach showed a high heterogeneity within hemocytes, but provides a detailed description of the different hemocyte transcriptomic populations in B. glabrata supported by distinct cellular functions and lineage trajectory. As a main result, scRNAseq revealed the 3 main population as a super-group of hemocyte diversity but, on the contrary, a great hemocytes plasticity with a probable capacity of hemocytes to engage to different activation pathways. This work opens a new field of research to understand the role of hemocytes particularly in response to pathogens, and towards S. mansoni parasites.